ELECTRICITY MARKET: PROBLEMS AND PROSPECTS - BUNIAK, OLEH; BABIUK, SERGIIY; OROBCHUK, BOGDAN; MOVCHAN, LEONID (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The article summarizes the theoretical aspects of the development of the new electric energy market, substantiated risks for the successful operation of market participants, and proposed solutions for deepening Ukraine's integration into the European energy market. It is shown that the reform of the electricity market of Ukraine is characterized by the transition from the "single buyer" market model to the national market model according to the standards of the European Union and the separation of the activities of electric energy transmission and distribution companies. The functioning of the wholesale market is based on bilateral contracts, and the feature of the retail market model is the possibility of freely choosing an electricity supplier.A theoretical assessment of the functioning of the energy market in new conditions was carried out, problems in the dynamics of electricity prices for household and non-household consumers were identified, and their impact on the tariff policy of Ukraine in the electricity generation sectors was substantiated. Analytical studies of the energy potential of the main segments of renewable energy sources have been conducted and the investment attractiveness of the development of low-carbon energy sources and the "green" economy has been shown.The main measures for deepening the integration of Ukraine with the energy market of the European Union and improving energy security are outlined, where the priorities are the creation of competition protection rules to ensure the balance of demand and supply in real time of the combined electric network by market participants, the formation of a centralized dispatch management system to ensure reliability, introduction of low-carbon technologies to reduce the costs of energy decarbonization, introduction of tariffs based on the regulatory base of assets, introduction of market mechanisms to stimulate the development of renewable energy sources.
Keywords: electricity market; wholesale market; distribution of electricity; energy system imbalance; distributed generation systems